Wages and Employees Performance: The Quality of Work Life as Moderator - Gunawan, Hendra; Amalia, Rezki (International Journal of Economics and Financial Issues, 2015)
The wage factor and the quality of working life needs to get the attention of the management to be able for improve the employees performance. This research aims to know the effect of wages on employees performance are moderated by the quality of work life. The type of the data being used is the primary data in the form of a questionnaire. Sampling is done by stratified random sampling of 100 employees in a manufacturing company. Data analysis using linear regression and moderated regression analysis (MRA). The result showed a significant negative effect on the wages of employees performance. Other finding is negative effect of wages which are moderated by the quality of work life is caused by the effect of intrinsic motivation (quality of working life) is more powerful than extrinsic motivation (wages). Quality of work life is quasi moderators that weaken the wages variable. Further research is recommended to expand the research by adding independent variable that affects the performance of employees. Keywords: wages; quality of work life; employees; performance; moderated regression analysis JEL Classification: J330